Fiscal Monitor, October 2020 : Policies for the Recovery. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2020)
Chapter 1 of the report draws some early lessons from governments' fiscal responses to the pandemic and provides a roadmap for the recovery. Governments' measures to cushion the blow from the pandemic total a staggering USD 12 trillion globally. These lifelines and the worldwide recession have pushed global public debt to an all-time high. But governments should not withdraw lifelines too rapidly. Government support should shift gradually from protecting old jobs to getting people back to work and helping viable but still-vulnerable firms safely reopen. The fiscal measures for the recovery are an opportunity to make the economy more inclusive and greener. Chapter 2 of this report argues that governments need to scale up public investment to ensure successful reopening, boost growth, and prepare economies for the future. Low interest rates make borrowing to invest desirable. Countries that cannot access finance will, however, need to do more with less. The chapter explains how investment can be scaled up while preserving quality. Increasing public investment by 1 percent of GDP in advanced and emerging economies could create 7 million jobs directly, and more than 20 million jobs indirectly. Investments in healthcare, housing, digitalization, and the environment would lay the foundations for a more resilient and inclusive economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet